Examining the Effects of Key Workplace Variables on Job Burnout of Southern Prison Staff - Leone, Matthew C. (The prison journal, 2024)
Burnout is a phenomenon commonly found in the workplace. When burnout is job-related, it is considered job burnout. Historically, job burnout has been most common among those who work in human services fields and who deal with stressful situations on a regular basis. Job burnout consists of three components: emotional exhaustion, depersonalization, and feelings of work ineffectiveness. While job burnout may be common, not all workers in stressful fields experience it, which indicates that there must be organizational or individual factors that limit the likelihood of job burnout for some workers. This study examined the impact of four job-related factors (job stress, job involvement, job satisfaction, and organizational commitment) on the three components of job burnout for correctional workers in a large, maximum-security prison in the Southern United States. The findings indicated that the four job-related factors were related strongly and in the predicted direction to two or three of the measures of job burnout.